Pengembangan media pembelajaran “BEJU” berbasis web melalui pendekatan saintifik untuk meningkatkan kemampuan berpikir kritis siswa - Achmad Alfaridzih; Muchammad Miftakhul Hakim; Lutfia Asyhadi; Tjie Yan Sufi Dewa Tapa Larantuka; Mila Rif’ati (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2024)
This research and development aims to produce BEJU learning media as a learning medium that contains material on maintaining honesty in Islamic Education subjects for class VII SMP, in particular. Media development is used as an alternative in developing information technology and internet-based media. This research and development uses the Sugiyono model which has gone through modifications including, (1) potential and problems, (2) data collection, (3) product design, (4) design validation, (5) design revision, (6) trial product, (7) product revision, (8) trial use, (9) product revision, (10) final product. Based on the results of validity tests and product trials on students, it was found that the BEJU learning media was categorized as very effective for being implemented as Islamic education learning media.